Pengembangan Potensi Usaha Dupa Menjadi Produk Unggulan - Sarwoko, Endi; Ahsan, Moh.; Nurfarida, Iva Nurdiana (Universitas Nusantara PGRI Kediri, 2020)
The aim of the community service program is to develop business potential in partner village, namely Petungsewu Village, Wagir District, Malang Regency, so that they can become the village's superior products. The problem faced by partner villages is the value added of incense products are still low because it only focuses on raw incense, does not have its own market, because incense production is still based on orders, and the availability of raw material is often lacking. The first solution is of producing incense fragrances is given a brand whose marketing applies a partnership pattern with successful incense entrepreneurs, the second solution is to assist brand design and brand registration, and the third solution is to increase production of bamboo sticks by machine. The approach in implementing this service is Community Based Participatory Research (CBPR), which is a collaborative approach with the aim of overcoming problems in the community. The method is used in the form of assistance and consultation for making incense and packaging carried out by partners from successful entrepreneurs, mentoring and consultation on trademark registration, and substitution of science and technology in the form of using a bamboo stick refiner. The result of the activity there was an increase in value added because it had been produced and sold fragrant incense with